On the irreversibility of time for an electromagnetic hereditary linear system - Matarazzo, G. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We give conditions for an electromagnetic linear system of hereditary type under which the time-reversal hypothesis does not hold if the relaxation functions of the electromagnetic field have different behavior at the extremes of the interval of definition. Under the same conditions, it is also possible to prove that these functions are constant if they have the same behavior at the extremes of the interval of definition.